1999
DOI: 10.1542/peds.104.6.e78
|View full text |Cite
|
Sign up to set email alerts
|

Technical Report: Minor Head Injury in Children

Abstract: ABSTRACT. Minor head trauma affecting children is a common reason for medical consultation and evaluation. In order to provide evidence on which to base a clinical practice guideline for the American Academy of Pediatrics, we undertook a systematic review of the literature on minor head trauma in children.Methods. Medline and Health databases were searched for articles published between 1966 and 1993 on head trauma or head injury, limited to infants, children, and adolescents. Abstracts were reviewed for relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
0
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 35 publications
(19 reference statements)
3
58
0
9
Order By: Relevance
“…Skull radiographs were abnormal in a lower frequency (2.5%) when compared to CCT scans and had a low sensitivity, which is in agreement with some studies that show its lack of importance as a routine screening study in patients with mild head trauma 17,[19][20][21] . lloyd et al 17 observed that neurological examination has a higher sensitivity than skull radiographs with respect to the investigation of intracranial lesions.…”
Section: Discussionsupporting
confidence: 86%
“…Skull radiographs were abnormal in a lower frequency (2.5%) when compared to CCT scans and had a low sensitivity, which is in agreement with some studies that show its lack of importance as a routine screening study in patients with mild head trauma 17,[19][20][21] . lloyd et al 17 observed that neurological examination has a higher sensitivity than skull radiographs with respect to the investigation of intracranial lesions.…”
Section: Discussionsupporting
confidence: 86%
“…Accordingly, algorithms for the evaluation and triage of children and adolescents with mTBI were set up (4,5 ) to reduce unnecessary CCT and inpatient observation. Even so, most CCT and short hospitalization can still be potentially avoided, because 93% of children with mTBI have no intracerebral lesions (6 ). An economic strategy was developed that was based on the use of biomarkers to support a reduction in unnecessary care, and there is a clear trend toward increased international efforts to evaluate the use of biomarkers in pediatric TBI (7)(8)(9).…”
mentioning
confidence: 99%
“…[7][8][9][10][12][13][14][15][16][17][18][19] Pasien dengan riwayat trauma kepala yang disertai penurunan kesadaran, kejang fokal, paresis, nyeri kepala dan muntah yang persisten, mempunyai indikasi kuat untuk dilakukan pencitraan kepala untuk mengetahui adanya perdarahan intrakranial. 18 Pemeriksaan yang sering digunakan adalah foto kepala, CT scan kepala dan Magnetic Resonance imagung (MRI) kepala.…”
Section: Diskusiunclassified
“…18 Pemeriksaan yang sering digunakan adalah foto kepala, CT scan kepala dan Magnetic Resonance imagung (MRI) kepala. [7][8][9][10][12][13][14][15][16][17][18][19] Foto kepala merupakan pemeriksaan yang relatif paling mudah tetapi mempunyai sensitifitas dan spesifitas yang bervariasi, sehingga sangat sulit untuk menarik suatu kesimpulan. Pemeriksaan CT scan kepala direkomendasikan pada pasien dengan penurunan kesadaran, kejang fokal, GCS kurang dari 13, fraktur tulang kepala.…”
Section: Diskusiunclassified